Emotions and Cognition of Dhildren with Autism Spectrum Disorders During the Covid-19 Pandemic - Siti Maemonah; Siti Maimuna; Kusmini Suprihatin; Dony Sulystiono; Fathimath Shifaza (International Journal of Advanced Health Science and Technology, 2022)
Children with autism spectrum disorder (ASD) often have difficulty controlling emotions, difficulty maintaining attention, relatively poor memory, and difficulty in speaking. Attention, memory, and speech are parts of cognition. During the covid-19 pandemic, individuals with autism feel more stressed because they have lost their routine. This type of research is quantitative descriptive with a cross sectional approach. The sampling technique is purposive sampling. The number of samples used were 59 ASD children aged 5-11 years. Emotional data was collected using the Positive and Negative Affect Schedule for Children, Short Form/PANAS-C-S scale, attention data was collected using the inattention subscale of the Swanson, Nolan, and Pelham scale, version IV (SNAP-IV), memory data was collected using the Observer questionnaire. Memory Questionnaire-Parent Form (OMQ-PF), and speech data were collected using the speech subscale of ATEC. The data obtained were analyzed descriptively. The results showed the average positive emotion (PA) of children with ASD = 18.20; negative emotional level (NA) = 12.42; emotion (PA + NA) = 5.78; inattention = 24.80; memory = 83.51; and speech = 26.71. The mean of positive emotions in ASD children is lower, negative emotions are higher, and overall good emotions are lower than normal children aged 8-11 years. The mean inattention score in children with ASD was included in the criteria for severe attention deficit symptoms. The mean memory of ASD children is lower than normal children aged 5-16 years. The average speech score of children with ASD is lower than the score normally achieved by normal children. The emotions and cognition of children with ASD during the covid-19 pandemic were lower than normal children. Efforts are needed to increase positive emotions and improve cognitive function which include: attention, memory, and speech in ASD children with various therapies that are suitable for each individual.